An observational study based on the interaction between the paediatric patient and radiographer. Issue 3 (August 2015) - Harding, J.; Davis, M.
Abstract Background The practice of paediatric radiography requires a completely different skill set to that of adult radiography. Often, obtaining a paediatric patient's cooperation is the most difficult aspect of the role. Ensuring that a child cooperates for the examination can make positioning easier, thereby potentially providing a more diagnostic image. Aim The aim of this study was to observe the interaction between the paediatric patient and the radiographer and to uncover techniques used by the radiographer to help alleviate any fear or stress that the child might have had. Method A direct observational method was conducted, after both the radiographer and the child's guardians provided full written consent. The actions of the radiographer and resultant reactions from the child were recorded on an observational checklist designed for paediatric examinations. Results Seventy-nine patients aged between three months to fifteen years and thirteen radiographers with no specific paediatric training other than experience were observed. Examinations observed included lower limb, upper limb, pelvis, abdomen and chest projections. The data gathered were the result of radiographer actions when interacting with both happy and sad children. Conclusions Successful methods of alleviating a child's fear and anxiety whilst in the X-ray room included the use of child friendly equipment such as colourful lead protection and posters on the wall, a simple explanation of what the equipment is before moving it, offering rewards such as stickers and praise and showing the child their image after the examination. When time was short and the workload was high, it was observed that radiographers were less likely to spend time calming the child down and instead were more focused on completing the examination as quickly as possible.